A literatura no ensino da leitura no 2º ciclo do ensino fundamental - RODRIGUES, Maria Delfina Carvalho (2019)
This work aims to address the importance of literature in reading practice. It also seeks to demonstrate the relevance that the school has for the student to develop reading practice. The act of reading is present everywhere in society. In this way, it is necessary to understand some factors that can interfere in the formation of competent readers. Therefore, in this study, we will highlight some ideas and perspectives regarding reading, taking into account the importance of encouraging it to cease being treated by many as something uninteresting. The present study, according to the nature of the data, is characterized as a bibliographical and qualitative research.